Clinical and Epidemiological Characteristics of Patients with Condilomatosis - Graciela Caridad Cabrera Acea; María Teresa Rodríguez Gandulla; Niurka Ramos Viera; Yoan Bernárdez Cruz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: Condyloma acuminatum is a common condition in our country and the world. It is considered to be a sexually transmitted infection, but it is commonly unreported. Objective: To determine the main clinical and epidemiological characteristics of patients with condilomatosis. Methods: A case series study was conducted in Health Areas number II, V and VII of Cienfuegos. The sample included 72 patients diagnosed with condyloma acuminatum. The following variables were analyzed: age, sex, educational level, residence area, location of lesions, number of sexual partners referred in the past 12 months, personal medical history of sexually transmitted infections and associated infections, sexual preferences and way of disease detection. Results: Genital condilomatosis was the most frequent infection. Females were predominant mostly between 20 and 39 years old (51.4%), while 55.6% (66.7%) of patients had achieved a secondary educational level and presented a personal medical history of sexually transmitted infections and associated infections prior to diagnosis. Concomitant infections were found in 23, 6% of patients: 70.6% of the cases presented bacterial vaginosis. Condyloma acuminatum was predominant in heterosexual patients and in those who reported between 2 and 3 sexual partners in the last 12 months. Most cases were diagnosed spontaneously. Conclusions: The clinical and epidemiological characteristics of patients diagnosed with condilomatosis in the Health Areas number II, V and VII are similar to those reported in other cases studied in the country and the world.